2004
DOI: 10.1007/s00428-004-1080-7
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 as a marker of intestinal EC-cells and related well-differentiated endocrine tumors

Abstract: Gastroenteropancreatic (GEP) endocrine tumors (ETs) are neoplasms showing different hormonal profiles and different clinical and prognostic features, which depend consistently on the site of origin. Histological features and general endocrine markers do not differentiate tumors in relation to their location, making it difficult to establish the site of origin of a GEP ET that has metastasized to the liver or lymph nodes. A site-specific marker would be particularly useful in the examination of small specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…Our studies show that the Cdx-2/3 gene is expressed at very low levels in the developing pancreas and in the adult islets. Furthermore, it is undetectable by immunocytochemistry because it has previously been reported in the adult rat and human ␣-cells as well as in glucagonomas (17). We also find that in ␣-TC1 cells, the Cdx-2/3 gene is not expressed clearly, indicating that it is dispensable for glucagon gene expression.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Our studies show that the Cdx-2/3 gene is expressed at very low levels in the developing pancreas and in the adult islets. Furthermore, it is undetectable by immunocytochemistry because it has previously been reported in the adult rat and human ␣-cells as well as in glucagonomas (17). We also find that in ␣-TC1 cells, the Cdx-2/3 gene is not expressed clearly, indicating that it is dispensable for glucagon gene expression.…”
Section: Discussionsupporting
confidence: 49%
“…Nevertheless, the expression of Cdx-2/3 in ␣-cells is not established. Although Cdx-2/3 has been reported to be present in ␣-cells of the adult mouse pancreas by immunocytochemistry (16), it is absent from the adult rat and human ␣-cells as well as from glucagonomas (10,17).…”
mentioning
confidence: 99%
“…Most studies have shown that CDX-2 is strongly and diffusely expressed in most ileal and appendiceal well-differentiated neuroendocrine tumors, with most studies demonstrating little to no staining in gastric, rectal, and pulmonary well-differentiated neuroendocrine tumors. [9][10][11][31][32][33] Relative few studies have included pancreatic tumors in their analysis of CDX-2 in well-differentiated neuroendocrine tumors. Barbareschi et al 9 demonstrated variable CDX-2 reactivity in 14/48 (29%) pancreatic well-differentiated neuroendocrine tumors, with staining limited to non-functioning tumors.…”
Section: Pax8 Expression In Neuroendocrine Tumorsmentioning
confidence: 99%
“…A staging system based on tumour size and invasion, lymph node metastasis, and distant metastasis showed prognostic value [25]. Immunohistochemical markers have also been proposed as prognostic indicators [26,27,28]. In this study, we showed that the WHO 2010 classification accurately predicts metastatic disease and the prognosis of rectal NETs.…”
Section: Discussionmentioning
confidence: 60%